PIWI proteins and their interactors in piRNA biogenesis, germline development and gene expression. Issue 2 (23rd June 2014) - Ku, Hsueh-Yen; Lin, Haifan
Abstract: PIWI-interacting RNAs (piRNAs) are a complex class of small non-coding RNAs that are mostly 24–32 nucleotides in length and composed of at least hundreds of thousands of species that specifically interact with the PIWI protein subfamily of the ARGONAUTE family. Recent studies revealed that PIWI proteins interact with a number of proteins, especially the TUDOR-domain-containing proteins, to regulate piRNA biogenesis and regulatory function. Current research also provides evidence that PIWI proteins and piRNAs are not only crucial for transposon silencing in the germline, but also mediate novel mechanisms of epigenetic programming, DNA rearrangements, mRNA turnover, and translational control both in the germline and in the soma. These new discoveries begin to reveal an exciting new dimension of gene regulation in the cell.